Study on the relationship between indoor ventilation frequency and anxiety and depression symptoms in older persons: based on the data of 2018 CLHLS - Lu Lin; Pingping He; Xiaohui Qiu; Sihui Qiu; Jiangping Chen; Jin Wang (BMC Geriatrics)
Abstract Background To investigate the association between indoor ventilation frequency and symptoms of depression and anxiety in older persons. Methods A binary logistic regression model was used to analyze the effects of indoor ventilation frequency on depression and anxiety by using data from the 2018 Chinese longitudinal healthy longevity survey (CLHLS). Results A total of 9,690 older persons with an average age of (83.20 ± 11.27) years were included, including 4,458 males (46.0%) and 5,232 females (54.0%). The average score of indoor ventilation frequency was (6.06 ± 1.98) points, including 770 people (7.9%) with low frequency, 3,066 people (31.6%) with medium frequency, and 5,854 people (60.4%) with high frequency. 842 (8.7%) had symptoms of depression and 204 (2.1%) had symptoms of anxiety. Compared with the older persons with low indoor ventilation frequency, the older persons with higher ventilation frequency had a lower incidence of depression (OR(95%CI) = 1.92 (1.50 ∼ 2.46), 1.51 (1.27 ∼ 1.79); P < 0.001). However indoor ventilation frequency was not associated with anxiety symptoms. Conclusion Indoor ventilation frequency is related to depressive symptoms in older persons. Communities and families should pay more attention to indoor ventilation and intervene in time to promote and improve the mental health of older persons.